2020
DOI: 10.1111/apps.12247
|View full text |Cite
|
Sign up to set email alerts
|

Attention‐Deficit Hyperactivity Disorder Symptoms and Entrepreneurial Orientation: A Replication Note

Abstract: There is a small body of literature linking attention‐deficit hyperactivity disorder (ADHD) and its symptoms to entrepreneurial manifestations. Some studies take a subclinical perspective by studying the presence of symptoms, while other studies take a clinical perspective by studying the formal diagnosis of ADHD. The entrepreneurial manifestations examined range from entrepreneurial intention to the choice to become self‐employed and from entrepreneurial orientation (EO) to entrepreneurial success. Despite it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 61 publications
4
35
5
Order By: Relevance
“…8. Since our sample was slightly older than related impulsivity-entrepreneurship studies (Dimic and Orlov, 2014;Wismans et al, 2020) and consisted of experienced owner-managers, we conducted additional multi-group analyses on age and ownership duration using an extreme group approach (Preacher et al, 2005). Splitting groups into lower and upper quartiles (age <43 years and >59 years; ownership duration <7 years and >19 years) revealed no substantive differences from the original multi-group analyses, indicating the overall relevance of our model to these more extreme demographic variations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8. Since our sample was slightly older than related impulsivity-entrepreneurship studies (Dimic and Orlov, 2014;Wismans et al, 2020) and consisted of experienced owner-managers, we conducted additional multi-group analyses on age and ownership duration using an extreme group approach (Preacher et al, 2005). Splitting groups into lower and upper quartiles (age <43 years and >59 years; ownership duration <7 years and >19 years) revealed no substantive differences from the original multi-group analyses, indicating the overall relevance of our model to these more extreme demographic variations.…”
Section: Discussionmentioning
confidence: 98%
“…Perhaps the most prominent development in this regard is emerging research linking attention deficit/hyperactivity disorder (ADHD) to higher entrepreneurial intention (EI) (Verheul et al, 2015), entrepreneurial orientation (Wismans et al, 2020) and nascent venturing (Lerner et al, 2019;Stappers and Andries, 2021), where impulsivity appears to be the underlying trait driving these results (Antshel, 2018;Wiklund et al, 2017). Impulsivity is a multidimensional construct encompassing four distinct impulsigenic traits, which predispose individuals to impulsive behaviours (Whiteside and Lynam, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Entrepreneurs who do not premeditate are less likely to feel fear and worry (Whiteside and Lynam 2001) when facing an uncertain opportunity because they tend to overlook the negative consequences (Wiklund et al 2017). Because of their focus on the upside potential rather than the downside risk, entrepreneurs with ADHD symptoms are also more likely to proactively engage in risky projects that have uncertain outcomes or high profits and losses and are thereby critical to entrepreneurial performance (Wismans et al 2020).…”
Section: Adhd Symptoms and Entrepreneurial Performancementioning
confidence: 99%
“…Some of the characteristics commonly associated with it are competitive aggressiveness, autonomy, capacity for innovation, proactivity and willingness to take risks (Aljanabi, 2018;Bolton, 2012;Fillis & Rentschler, 2010;Rauch et al, 2009; S. Robinson & Stubberud, 2014) Studying the relationship between Impulsivity and Entrepreneurial Orientation showed that sensation seeking and a lack of premeditation generally have a positive influence on entrepreneurship (Wiklund et al, 2017). These authors conclude that Impulsivity is positive for Entrepreneurial Orientation and that sensation seeking is related to curiosity and is intrinsic to motivation (Collins et al, 2004;Wismans et al, 2020;Zuckerman, 1994). Robinson (2008) indicates that entrepreneurs need to be curious, feel challenged and, consequently, adapt to change, which drives them to be seekers of new opportunities.…”
Section: Introductionmentioning
confidence: 99%